2020
DOI: 10.1371/journal.pone.0229946
|View full text |Cite
|
Sign up to set email alerts
|

Oral health treatment habits of people with schizophrenia in France: A retrospective cohort study

Abstract: ObjectiveTo identify the differences between persons with schizophrenia (PWS) and general population in France in terms of oral health treatment (tooth scaling, dental treatment and tooth extraction) and the factors associated with these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
3
18
0
1
Order By: Relevance
“…Sample size was determined by power analysis. Variance estimates for the primary outcome measurement, plaque index scores, were based on the work of Almonani et al [ 22 ], with a meaningful difference of 24% as effect size, and with a type I error at 0.05 and power at 0.80. The result showed that 30 subjects were needed to be recruited in each group with assumed participant dropout rate of approximately 30%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was determined by power analysis. Variance estimates for the primary outcome measurement, plaque index scores, were based on the work of Almonani et al [ 22 ], with a meaningful difference of 24% as effect size, and with a type I error at 0.05 and power at 0.80. The result showed that 30 subjects were needed to be recruited in each group with assumed participant dropout rate of approximately 30%.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, oral health is often neglected by psychiatric personnel and the patients themselves [ 13 ]. Despite their worsening oral health, these patients receive less dental treatment than the general population [ 21 , 22 ]. To date, only a few studies have investigated the effects of oral health education or interventions on people with SMI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fear of mental illness, difficult access to private practice, and the high cost of dental care are additional barriers that contribute to poor oral health and OHRQoL. 9 Oral health programs, although presenting statistically significant results, have little clinical impact on oral health. 10 Khokhar et al 11 studied schizophrenics and found no study with a sufficiently high level of proof to support current practices in oral health education for PWS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their worsening oral health, these patients receive less dental treatment than the general population [21,22]. To date, only a few studies have investigated the effects of oral health education or interventions on people with SMI.…”
Section: Introductionmentioning
confidence: 99%